Boundary-layer flow of nanofluids over a moving surface in a flowing fluid - Bachok @ Lati, Norfifah; Ishak, Anuar; Pop, Ioan (Elsevier, 2010)
The steady boundary-layer flow of a nanofluid past a moving semi-infinite flat plate in a uniform free stream is investigated. The plate is assumed to move in the same or opposite directions to the free stream. The resulting system of nonlinear ordinary differential equations is solved numerically using the Keller-box method. Numerical results are obtained for the skin-friction coefficient, the local Nusselt number and the local Sherwood number as well as the velocity, temperature and the nanoparticle volume fraction profiles for some values of the governing parameters, namely, the plate velocity parameter, Prandtl number, Lewis number, the Brownian motion parameter and the thermophoresis parameter. The results indicate that dual solutions exist when the plate and the free stream move in the opposite directions.